ANALSIS KENYAMANAN TERMAL DAN PERSEPSI PENGUNJUNG TERHADAP RUANG TERBUKA HIJAU DI KAMPUS SUDIRMAN UNIVERSITAS UDAYANA - Cantika Indraswari; Anak Agung Ayu Oka Saraswati; I Nyoman Susanta (Jurnal Arsitektur ARCADE, 2025)
Abstract:Thermal comfort in campus green open spaces (GOS) plays an important role in supporting the academic and social activities of the academic community, especially in tropical regions such as Denpasar. This study aims to analyze thermal comfort and visitor perceptions of the GOS at Sudirman Campus, Udayana University. The research uses a quantitative approach through the collection of microclimate parameters (air temperature, humidity, wind speed, and surface temperature) and user perception surveys. Comfort data is analyzed using the Temperature Humidity Index (THI), while perception data is analyzed descriptively. The results show that thermal comfort varies significantly between locations. Locations with denser vegetation and natural ground surfaces show lower THI values and higher comfort levels. User perceptions support these findings, indicating that the physical condition of the GOS greatly affects comfort. This study recommends the addition of natural shading elements and increased vegetation as design strategies for GOS that are more responsive to tropical climates Keywords: thermal comfort, green open space, user perception, THI, campus Abstrak: Kenyamanan termal dalam ruang terbuka hijau (RTH) kampus memainkan peran penting dalam mendukung aktivitas akademik dan sosial, khususnya di wilayah tropis seperti Denpasar. Penelitian ini bertujuan untuk menganalisis kenyamanan termal dan persepsi pengunjung terhadap RTH di Kampus Sudirman Universitas Udayana. Data dikumpulkan melalui pengukuran parameter mikroklimat (suhu udara, kelembaban, kecepatan angin, dan suhu permukaan) serta survei persepsi pengguna. Indeks kenyamanan dihitung menggunakan Temperature Humidity Index (THI), sedangkan data persepsi dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa area dengan tutupan vegetasi yang tinggi dan permukaan alami cenderung memiliki nilai THI yang lebih rendah dan persepsi kenyamanan yang lebih tinggi. Studi ini merekomendasikan penambahan elemen peneduh alami dan peningkatan vegetasi sebagai strategi desain RTH yang responsif terhadap iklim tropis. Kata Kunci: kenyamanan termal, ruang terbuka hijau, persepsi pengguna, THI, kampus